Optimizing the application of a novel harvest aid to improve the quality of mechanically harvested cotton in the North China Plain - Lu MENG; Li-zhen ZHANG; Hai-kun QI; Ming-wei DU; Yan-li ZUO; Ming-cai ZHANG; Xiao-li TIAN; Zhao-hu LI (Journal of Integrative Agriculture)
Defoliation is an indispensable step in cotton production with mechanical harvesting, especially in the North China Plain (NCP) where mechanical harvesting is limited by a large proportion of green leaves and unopened bolls at harvest time due to insufficient thermal resources. It is essential to quantify the optimal use of defoliation products while minimizing yield and quality loss in China. The objective of this study was to test the effect of a new defoliant Xinsaili (XSL, a compound of 10% thidiazuron and 40% ethephon) on the spatial distribution of cotton leaves and bolls, yield and quality in the NCP. There were four treatments: XSL 1800 mL ha–1, XSL 2700 mL ha–1, XSL splitted into two equal applications (1350 mL ha–1 for each), and XSL-free (water) control. Field experiments were conducted in Hebei, China in 2016–2017. All the defoliant treatments did not significantly affect cotton yield and fiber quality compared with the water control. At harvest time, the rate of open bolls under XSL 2700 mL ha–1 was 13.5% higher than that under XSL-free control, while the other two treatments showed no significant difference, across the two years. Defoliation percentage of the three XSL treatments showed no difference, but they were on average 42.2% higher than that of XSL-free control. The year-round effect of the defoliant XSL was significant, indicating that climate factors would affect its application. It was concluded that the optimal dose of XSL in the NCP was 2700 mL ha–1, and it was unnecessary to split it into two applications. These results would promote cotton mechanical harvesting and reduce the labor cost of cotton production in China.